Acute Treatment of Traumatic Tattooing With Dermabrasion: A Case Report - Khalifa Al Alawi; Alreem Al Khayarin; Hanaa Al Kalbani; Sultan Al Shaqsi (Case Reports in Dermatological Medicine)
Traumatic tattoos result from foreign particles embedding into the dermis, often following industrial accidents or explosions. Among available treatments, including laser therapy and surgical excision, dermabrasion remains a cost-effective and widely accessible option. We present the case of a 49-year-old female construction supervisor who sustained extensive facial traumatic tattooing from the explosion of a hydraulic cement mixer. Clinical examination identified deeply embedded cement particles with localized erythema and edema on the left face. Following stabilization, she underwent acute dermabrasion under general anesthesia, employing staged removal of superficial and partial dermal layers to optimize particle clearance while preserving viable tissue. At 3-month follow-up, the patient demonstrated substantial reduction of pigmentation, minimal scarring, and high satisfaction. Dermabrasion, traditionally applied to superficial dermal lesions, proved particularly effective in this acute context by limiting chronic pigmentation, fibrosis, and textural irregularities. Compared to laser therapy, which requires multiple sessions and carries risk of incomplete clearance in particulate-laden wounds, or surgical excision, which may cause contour deformity, dermabrasion offers immediate, broad-surface intervention with relatively low morbidity. This case underscores dermabrasion’s value as a first-line modality for acute traumatic tattoos, especially where resources constrain advanced laser platforms. Prompt recognition and intervention are critical to outcome, and while further research should refine timing, technique, and adjunctive care, dermabrasion remains a pragmatic, effective option in managing acute dermal trauma with embedded particulate matter.